RECURSOS HÍDRICOS EM QUESTÃO: VIVÊNCIAS E PRÁTICAS NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL - Márcia Barbosa (TRF2, 2017)
One of the most impacted natural resource by environment degradation and by climate changes is water. In Brazil, water crisis has led the most populous area to rationing and has implicated severely in productive systems, demanding changes in millions of people consumption. On this scenario, it is presented the-fourth-year-elementary-public-school-research, in Rio de Janeiro, on critical attitude regarding the use and preservation of water in daily life. Action-research was the methodology adopted, in which the activities were developed by an environmental education project, prioritizing experience, debate and search for knowledge and problem solutions. The theoretical basis was on documents and authors who speak about environment and childhood cognitive development. The research findings indicated that the activity proposals have contributed for knowledge development and fighting the waste and pollution of the resource.